2022
DOI: 10.4103/sjoh.sjoh_21_22
|View full text |Cite
|
Sign up to set email alerts
|

Approach to Pediatric Esophageal Foreign Body Ingestion

Abstract: Background: Foreign body (FB) ingestion is a frequent home accident in the pediatric population and is one of the leading causes of morbidity and mortality in children. We aimed to describe the problem of pediatric esophageal FB ingestion at King Abdulaziz University Hospital over 10 years regarding patient, visit, and management characteristics and identify the pediatric specialty team that was called first to the emergency department in such cases. Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Coins were the most frequent FBs (48.2%), and most FBs (63.6%) affected the upper esophagus. 9 Similarly, a study from the Jazan region showed that 68.5% of FBs ingested were coins. They also found that the incidence of removal of coin FB ingestion markedly increased after coin currency implementation from 16.1% of all cases to 83.9%.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Coins were the most frequent FBs (48.2%), and most FBs (63.6%) affected the upper esophagus. 9 Similarly, a study from the Jazan region showed that 68.5% of FBs ingested were coins. They also found that the incidence of removal of coin FB ingestion markedly increased after coin currency implementation from 16.1% of all cases to 83.9%.…”
Section: Discussionmentioning
confidence: 98%
“…Coins are commonly located at C1-C6, thereby confirming a highly statistically significant relationship between FB type and CXR characteristic findings, as the sensitivity to detecting coins in x-rays was 100%, which is consistent with the findings of other studies. 9,16 In other studies, the FB was not visualized by x-ray in 43% of cases, and this was related to the different characteristics of the FB. 13 The need for intervention depends on the characteristics of the ingested FB, time of impaction to decrease complications, and location.…”
mentioning
confidence: 86%
See 1 more Smart Citation